الأهمية الاستراتجية للبترول الجزائري - العبسي, علي; شيخي, بلال (جامعة الوادي - University of Eloued, 2017)
يمثل قطاع البترول أحد القطاعات الإنتاجية الهامة في معظم الاقتصاديات، ولقد رزكزت هذه الورقة البحثية إلى نشأة وتطور البترول في الجزائر وكذا الأهمية الاستراتجية للبترول وقد توصلت الدراسة إلى أن حدوث التغيرات التكنولوجية يمكن أن يؤثر جوهريا على تحسين معدلات أداء وعرض المنتجات والخدمات في القطاعات الإنتاجية . The oil sector is one of the most important productive sectors in most economies. The paper focuses on the development and development of oil in Algeria as well as the strategic importance of petroleum. The study concluded in previous parts that technological changes can significantly affect the performance of products and services in the sectors Productivity
The strategic importance of Algerian oil
مقال
Keywords: البترول في الجزائر- الأهمية الاستراتجية للبترول الجزائري; Oil in Algeria - The strategic importance of Algerian oil